Kebijakan Program Sertifikasi Peningkatan Profesionalisme Guru SD PAI di Desa Mogolaing Kota Kotamobagu - Tahalu, Abulfidan; Anugrah Lestari; Buhungo, Ruwiah Abdullah (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This article discusses the Policy of the Islamic Religious Education Teacher Certification Program for Elementary Schools in Mogolaing Village. The method used in this study is a qualitative approach.With this type of field research and using a case study approach. Data collection is carried out by means of interviews, observation, and documentation. The source of data in this study is the Head of the General Division of the Kotamobagu City Education Office, the Head of the Islamic Education Section of the Ministry of Religious Affairs of Kotamobagu City, the Principal at Elementary Schools Mogolaing, and the Teacher of Islamic Education at Mogolaing Elementary School. The results showed that in Elementary Schools Mogolaing there are two certified Islamic Education teachers, namely teachers at Elementary Schools 2 Mogolaing and Elementary Schools 3 Mogolaing. Teacher certification programs can improve teacher professionalism. And one of the factors that influence that is the certification allowance. So in addition to improving teacher welfare, certification is also a motivation for teachers to work harder. The teacher must have the awareness that the government has given him a stipend so that he must be able to work more than other teachers who have not been certified. In addition, being a certified teacher requires teachers to be more professional at work because they hold the title of certified teacher.